Low-energy plasma immersion ion implantation to induce DNA transfer into bacterial E. coli - K. Sangwijit (2018)
© 2015 Elsevier B.V. Plasma immersion ion implantation (PIII) at low energy was for the first time applied as a novel biotechnology to induce DNA transfer into bacterial cells. Argon or nitrogen PIII at low bias voltages of 2.5, 5 and 10 kV and fluences ranging from 1 × 1012to 1 × 1017ions/cm2treated cells of Escherichia coli (E. coli). Subsequently, DNA transfer was operated by mixing the PIII-treated cells with DNA. Successes in PIII-induced DNA transfer were demonstrated by marker gene expressions. The induction of DNA transfer was ion-energy, fluence and DNA-size dependent. The DNA transferred in the cells was confirmed functioning. Mechanisms of the PIII-induced DNA transfer were investigated and discussed in terms of the E. coli cell envelope anatomy. Compared with conventional ion-beam-induced DNA transfer, PIII-induced DNA transfer was simpler with lower cost but higher efficiency.